EXTRINSIC ELEMENT ANALYSIS OF THE MOVIE BILA ESOK IBU TIADA - yulianda, Asri; Ray, Sukma Adelina (LUMBUNG AKSARA, 2024)
This study aims to analyze the extrinsic elements in the film Bila Esok Ibu Tiada based on the literary sociology approach proposed by Wellek and Warren. This film raises the theme of a mother's sacrifice, the value of solidarity in the family, and social change due to modernization. By using descriptive qualitative method, this research examines three main aspects in literary sociology, namely the sociology of authors, the sociology of literary works, and the sociology of readers. The analysis shows that the background of the author, Nuy Nagiga, who has journalistic experience, contributes to building the realism of the story. In terms of the sociology of literary works, the movie illustrates the challenges faced by single mothers and the impact of social change on family values. Meanwhile, in terms of the sociology of readers, the movie succeeds in building the audience's emotions and encourages reflection on family relationships. Overall, this study shows that extrinsic elements have an important role in shaping the meaning and impact of a literary work in the form of a movie.